Imaging of Cardiac Transplantation: An Overview - Clemmensen, Tor Skibsted; Jensen, Niels Møller; Eiskjær, Hans (Seminars in nuclear medicine, 2021)
Heart transplantation (HTx) remains the optimal treatment for selected patients with end-stage advanced heart failure. However, survival is limited early by acute rejection and long term by cardiac allograft vasculopathy (CAV). Even though the diagnosis of rejection is based on histology, cardiac imaging provides a pivotal role for early detection and severity assessment of these hazards. The present review focuses on the use and reliability of different invasive and non-invasive imaging modalities to detect and monitor CAV and rejection after HTx. Coronary angiography remains the corner stone in routine CAV surveillance. However, angiograms are invasive and underestimates the CAV severity especially in the early phase. Intravascular ultrasound and optical coherence tomography are invasive methods for intracoronary imaging that detects early CAV lesions not evident by angiograms. Non-invasive imaging can be divided into myocardial perfusion imaging, anatomical/structural imaging and myocardial functional imaging. The different non-invasive imaging modalities all provide clinical and prognostic information and may have a gatekeeper role for invasive monitoring. Acute rejection and CAV are still significant clinical problems after HTx. No imaging modality provides complete information on graft function, coronary anatomy and myocardial perfusion. However, a combination of invasive and non-invasive modalities at different stages following HTx should be considered for optimal personalized surveillance and risk stratification.